Role of Women’s Organisations in Revitalising Communities: Some Reflections from the Gujarat Earthquake, India - Smita Mishra Panda (International Journal of Modern Agriculture, 2020)
This paper is based on the Gujarat earthquake of 2001 in which there was extensive devastation in Kachchh district in which more than 20,000 lives were lost. It has been almost 2 decades since the disaster and the analysis presented in the paper is a reflection on the role of women’s organization in revitalizing the communities. Invariably, women are the most adversely affected, vulnerable to any disaster and they struggle to revitalise their lives and livelihoods typically in a patriarchal setup against a declining resource base. In case of Kachchh, several grassroot organisations have been consistently working with the community women in the villages and have been able to solicit their participation successfully for all the major and specific measures of rehabilitation. Continuation of the livelihood development has been the key to involve women in revitalizing communities. The paper also provides some key lessons learnt from the mutual interaction of women’s organisations, with women at the community level during times of disaster.